The boss is not always right: Norwegian preschoolers do not selectively endorse the testimony of a novel dominant agent. Issue 3 (27th December 2021) - Fonn, Erik Kjos; Zahl, Joakim Haugane; Thomsen, Lotte
Abstract: Theories of cultural evolution posit that cues of competence‐based prestige, rather than formidability‐based dominance, should guide culturally transmitted learning, but recent work suggested that French and Kaqchikel Guatamalan preschoolers place their epistemic trust in dominant others. In contrast, this study shows that 249 three‐ to six‐year‐olds (116 girls, tested between 2016 and 2018 across metropolitan locations with varying ethnic composition and socioeconomic status) randomly endorsed the word‐labels of dominant and subordinate agents in the egalitarian culture of Norway, using stimuli which solicit dominance inferences among infants and manipulating anonymity across studies to control for egalitarian desirability bias. A meta‐analysis estimated that 48% endorsed the dominant's testimony. This demonstrates that the tendency to endorse the epistemic claims of dominant individuals does not emerge reliably in early childhood.